2014
DOI: 10.1039/c3em00719g
|View full text |Cite
|
Sign up to set email alerts
|

Composition and sources of fine particulate matter across urban and rural sites in the Midwestern United States

Abstract: The composition and sources of fine particulate matter (PM2.5) were investigated in rural and urban locations in Iowa, located in the agricultural and industrial Midwestern United States from April 2009 to December 2012. Major chemical contributors to PM2.5 mass were sulfate, nitrate, ammonium, and organic carbon. Non-parametric statistical analyses demonstrated that the two rural sites had significantly enhanced levels of crustal materials (Si, Al) driven by agricultural activities and unpaved roads. Meanwhil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
67
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 55 publications
5
67
1
2
Order By: Relevance
“…Particulate matter with aerodynamic diameters less than 2.5 lm (PM 2.5 ) has been studied extensively as it is associated with air quality issues, particularly in urban areas (Huang et al 2013;Kundu and Stone 2014). PM 2.5 can easily penetrate into the respiratory organs of the human body which may lead to health problems and even mortality (Dockery et al 1993;Pope et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter with aerodynamic diameters less than 2.5 lm (PM 2.5 ) has been studied extensively as it is associated with air quality issues, particularly in urban areas (Huang et al 2013;Kundu and Stone 2014). PM 2.5 can easily penetrate into the respiratory organs of the human body which may lead to health problems and even mortality (Dockery et al 1993;Pope et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few studies have chemically characterized atmospheric aerosols in the rural Great Lakes region of the United States (Sheesley et al, 2004;Kim et al, 2005Kim et al, , 2007Zhang et al, 2009;Jeong et al, 2011;Sjostedt et al, 2011;Kundu and Stone, 2014;Bullard et al, 2017). Except for the major metropolitan areas of Detroit (MI), Chicago (IL), Minneapolis (MN), and Milwaukee (WI), much of the land is characterized by rural agricultural areas and remote forests without significant anthropogenic emissions.…”
mentioning
confidence: 99%
“…Studies across rural Illinois and Ohio found major atmospheric contributions from secondary sulfate, nitrate, and OC, consistent with aerosol aging during transport (Kim et al, 2005(Kim et al, , 2007Zhang et al, 2009), though these locations were much less forested than the more northern Great Lakes regions. Kundu and Stone (2014) measured composition and sources at rural locations in Iowa, identifying major PM mass contributions from biomass burning, combustion, and dust. Jeong et al (2011 identified contributions from SOA, elemental carbon, and dust in rural Harrow, Ontario, downwind of Detroit and Windsor.…”
mentioning
confidence: 99%
“…Relatively few studies have chemically characterized atmospheric aerosols in the rural Great Lakes region of the United States (Sheesley et al, 2004;Kim et al, 2005;Kim et al, 2007;Zhang et al, 20 2009;Jeong et al, 2011;Sjostedt et al, 2011;Kundu and Stone, 2014;Bullard et al, 2017). Except for the major metropolitan areas of Detroit (MI), Chicago (IL), Minneapolis (MN), and Milwaukee (WI), much of the land is characterized by rural agricultural areas and remote forests without significant anthropogenic emissions.…”
Section: Introduction 10mentioning
confidence: 99%
“…Studies across rural Illinois and Ohio found major atmospheric contributions from secondary sulfate, nitrate, and organic carbon, consistent with aerosol aging during transport (Kim et al, 2005;Kim et al, 2007; locations were much less forested than the more northern Great Lakes regions. Kundu and Stone (2014) measured composition and sources at rural locations in Iowa, identifying major PM mass contributions from biomass burning, combustion, and dust. Jeong et al (2011) and (Sjostedt et al, 2011) identified contributions from secondary organic aerosol, elemental carbon, and dust in rural Harrow, Ontario, downwind of Detroit and Windsor.…”
Section: Introduction 10mentioning
confidence: 99%